TINGKAT KEPATUHAN PENGGUNAAN OBAT ANTIDIABETES ORAL DENGAN MENGGUNAKAN METODE PILL-COUNT PADA PASIEN PROLANIS SISTEM JAMINAN KESEHATAN INDONESIA (JKN) DIABETES MELLITUS TIPE 2 DI POLIKLINIK RS SATRIA MEDIKA PERIODE MARET – APRIL 2023 - Meryta, Aries; Sabrina, Alifa; Eka Sari, Putri; Tuahuns, Farida; Savitri, Fitri; Listyawati, Mega (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Diabetes mellitus is a disease caused by increased blood sugar level due to lifestyle patterns or heredity. BPJS has a chronic program (PROLANIS) under the Health Insurance System (JKN) to control patient clinical parameters, prevent complications, and improve patient quality of life by monitoring patient compliance with treatment every month. This research was analyzed using the Pill-Count method, which is a method used to measure patient compliance in taking medication based on the remaining medication the patient has taken until the control date or return to the hospital. The assessment category is considered compliant if the percentage result is more than 80%. This type of research is observational with a cross-sectional approach. The total sample obtained was 37 patients in the March-April 2023 period at Satria Medika Hospital using the total sampling technique. The level of compliance based on the Pill-Count method shows that 14 patients (37.84%) were non-compliant and 23 patients (62.16%) were compliant. Based on the research results, it can be concluded that Satria Medika Hospital with the chronic program (PROLANIS) in March-April 2023 was in the non-compliant category as it achieved a compliance percentage of 62.16% (below the 80% threshold) using the Pill-Count method.